Formative Assessment Practices of Physics Teachers in Pakistan - Khan, M.; Zaman, T. U.; Saeed, A. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
Formative assessment is an ongoing activity that helps to understand the gaps between a student’s current understanding and the objectives to achieve. If combined with appropriate feedback, it has powerful positive impact on students’ learning. The objective of the study was to explore the quality of classroom assessment practices of physics teachers in Pakistan. One hundred fifteen (115) principals, one hundred thirty-nine (139) physics teachers and eight hundred (800) 10th class science students were selected randomly from 162 target schools. Three (03) validated and reliable 5-point Liker-type scales were developed to collect the perceptions of the respondents. Eighteen hundred checked class tests of 20 physics teachers were also analysed to explore the quality of assessment. It was concluded that the quality of formative assessment is poor, and teachers must be trained to improve feedback process given to the students to enhance their learning.